Effect of high hydrostatic pressure on aroma volatile compounds and aroma precursors of Hami melon juice - Pei, Longying; Liu, Wei; Jiang, Luxi; Xu, Heng; Liu, Luping; Wang, Xiaoyu; Liu, Manli; Abudureheman, Buhailiqiemu; Zhang, Heng; Chen, Jiluan (Frontiers in Nutrition, 2023)
High hydrostatic pressure (HHP) treatment is an effective technique for processing heat-sensitive fruits and causes changes in volatile compounds and their precursors while maintaining quality. We investigated the changes and correlations of volatile compounds, related enzyme activities and precursor amino acids, and fatty acids in Hami melon juice under 350–500 MPa pressure. The application of HHP treatment resulted in a considerable reduction of esters and a substantial increase in aldehydes and alcohols in C6 and C9. Activities of lipoxygenase (LOX), alcohol acyltransferase (AAT), and phospholipase A2 (PLA2) were lower than those of the untreated group, alcohol dehydrogenase (ADH) activity was reversed. When compared to fresh cantaloupe juice, there was an increase in both the types and contents of amino acids with lower total fatty acid contents than the control group. Positive correlations were observed among six ester-related substances and eight alcohol-related substances. Additionally, the correlations between volatile compounds and fatty acids were more substantial compared to those between volatile compounds and amino acids. HHP treatment increases Hami melon flavor precursors and is an effective way to maintain the aroma volatile compounds and flavor of Hami melon juice.